Pembendaharaan Kata Peserta Didik yang di Pengaruhi oleh Media Sosial di MI Hasyim As’ari Kelas 5 C - Syauqiatul Latifah; Ilmi Amalia Maghfiroh; Esa Nur Faizah (STIKes Ibnu Sina Ajibarang, 2025)
The development of digital technology has made social media an integral part of children's lives, including students of Madrasah Ibtidaiyah (MI). This study aims to explore the impact of social media on the language patterns of class 5C students at MI Hasyim Asy'ari. Using a qualitative method with a case study approach, data were obtained through semi-structured interviews and participant observations of 14 students who regularly access social media. The findings show that platforms such as TikTok, Instagram, and YouTube are the main sources of new vocabulary acquisition, such as the terms